Mapping of Rice Field Distribution in 2024 Based on 2019 Data from Menyuke District, Landak Regency - Juniansyah, Muhammad Andira; Anasi, Putri Tipa; Christanto, Ludovicus Manditya Hari (Universitas Tanjungpura, 2025)
Land conversion in Menyuke District of Landak Regency is a problem that can threaten the potential of food agricultural land, as well as food security. This research aims to map the distribution of agricultural land, especially paddy fields. This research uses remote sensing method with descriptive quantitative research form. The population in this study is the entire utilization of paddy fields in the menyuke sub-district covering an area of 3,240 Ha divided into irrigated paddy fields and rainfed paddy fields with a total of 80 sample points of paddy fields. The results of this study showed that irrigated paddy fields experienced a change in the area of paddy fields to 1,100.79 Ha where there was an increase in area of 211.75 Ha and also rainfed paddy fields experienced a change in the area of paddy fields to 1,794.71 where there was an increase in area of 262.51 Ha so that the total area of paddy fields in the menyuke sub-district in 2024 increased to 3,359.55 Ha. this data shows a significant increase in paddy fields.